2012
DOI: 10.1098/rsob.120072
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Na + and higher K + channel expression and function contribute to right ventricular origin of arrhythmias in Scn5a+/− mice

Abstract: Brugada syndrome (BrS) is associated with ventricular tachycardia originating particularly in the right ventricle (RV). We explore electrophysiological features predisposing to such arrhythmic tendency and their possible RV localization in a heterozygotic Scn5a+/− murine model. Nav1.5 mRNA and protein expression were lower in Scn5a+/− than wild-type (WT), with a further reduction in the RV compared with the left ventricle (LV). RVs showed higher expression levels of Kv4.2, Kv4.3 and KChIP2 in both Scn5a+/− and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
42
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(45 citation statements)
references
References 61 publications
3
42
0
Order By: Relevance
“…We subsequently compared our BrS gene expression profile with published reports of human cardiac tissue gene expression and noted commonalities. We observed a relative reduction in SCN5A gene expression in BrS iPSC-CMs compared to controls, which has been documented in both human and mouse tissue gene expressions studies (31,40). Furthermore, we noted a marked reduction in thlevels of KCND3 , which is congruent with human tissue studies from BrS patients that demonstrated marked down regulation of the Kv4.3 associated gene (31).…”
Section: Discussionsupporting
confidence: 73%
“…We subsequently compared our BrS gene expression profile with published reports of human cardiac tissue gene expression and noted commonalities. We observed a relative reduction in SCN5A gene expression in BrS iPSC-CMs compared to controls, which has been documented in both human and mouse tissue gene expressions studies (31,40). Furthermore, we noted a marked reduction in thlevels of KCND3 , which is congruent with human tissue studies from BrS patients that demonstrated marked down regulation of the Kv4.3 associated gene (31).…”
Section: Discussionsupporting
confidence: 73%
“…28,29 Finally, some studies have suggested that I Na might be smaller in RV than LV. 23,35 At the cellular level, APs showed deeper notches, shorter APDs at 50 % and 95 % of repolarisation and less APD prolongation on slowing of the pacing rate in RV than LV, 27,24,29 consistent with the larger I to and I Ks . Similarly, duration of monophasic APs in vivo was shorter in RV than in LV.…”
Section: Differences In Ion Channel Propertiesmentioning
confidence: 95%
“…A mouse model with heterozygous knock-out of SCN5A has also suggested that the RV might be particularly sensitive to loss of functional Na + channels, with a larger reduction in I Na in RV compared with LV. 23 Similarly, Veeraraghavan and Poelzing 35 showed that heterogeneity in Na v 1.5 expression in guinea pig may become a significant determinant of conduction heterogeneities under conditions where I Na is functionally reduced. However, this study also highlights that conduction heterogeneities can be further modulated by interventricular differences in other ion channels, including I K1 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…5 She finally demonstrated the molecular mechanism for these right ventricular changes using reverse transcription polymerase chain reaction, Western blots, and functional ionic current analysis through a specific reduction in right ventricular expression of Na + compared to K + channels in the Scn5a +/-hearts producing both slowed conduction and repolarisation heterogeneity. 6 Dr Martin's prize-winning research was carried out in the Physiological Lab, University of Cambridge, Cambridge, England, where she worked in the group of Professor Christopher Huang, MD, PhD, alongside the group of Andrew Grace, FRCP, PhD, in the Biochemistry Department. She also collaborated with several other centres: Cesare Terracciano, MD, PhD, and his group, Heart Science Centre, Imperial College London, London, on cardiac myocyte isolation and patch-clamp experiments; Professor Ming Lei, DPhil, and his group, Institute of Cardiovascular Sciences, University of Manchester, Manchester, England, on multielectrode mapping experiments; Cristina Rada, PhD, and her group, Medical Research Council Lab of Molecular Biology, Cambridge, on Western blot experiments; and Nicola Brice, PhD, and her group at Takeda Cambridge Limited on reverse transcription polymerase chain reaction experiments.…”
Section: Responses From Other Stakeholdersmentioning
confidence: 99%